FeCrMnNiCSi Coating on Grey Cast Iron FC 25 Variable Gas Pressure on Thermal Arc Spray Method - Purwaningsih, Hariyati; Putra, Rifqi Tantyo; Raharjo, Slamet; Rochiem, Rochman; Purniawan, Agung (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
One of the important components of motor fuel engine is cylinder liner. There is a compression and friction combustion process with a piston that produces mechanical energy in cylinder liner. This process introduced several problems that often arise, such as wear reducing because the piston is moving back and forth continuously causing gas leakage so that compression pressure is reduced. To prevent such damage it is necessary to coat the metal with other material that has better wear resistance. This study used FeCrMnNiCSi coating material deposited on Gray cast iron FC 25 by thermal arc spray method to analyze the influence of pressure air variation on morphology and mechanical properties. SEM analysis showed that the higher pressure on the coating process results smaller particles thereby decreasing the porosity. Roughness testing also showed a decrease in the higher pressure, at a pressure of 6 bar of 127.333 μm. Microhardness showed that the 6 bar pressure indicating hardness was 639.8 HV. At 6 bar pressure also obtained the highest abrasion resistance value is 29.66 rotation / mg. The value of adhesion strength in the 4 bar pressure variables shows the optimum value compared with other pressure variations of 15.02 MPa. Keywords: cylinder liner, thermal arc-spray, pressure ambient